A hemoperfusion column selectively adsorbs LAP+ lymphocytes to improve anti-tumor immunity and survival of tumor-bearing rats - Kazuo Teramoto; Yuji Ueda; Ryosuke Murai; Kazumasa Ogasawara; Misako Nakayama; Hirohito Ishigaki; Yasushi Itoh (PLoS ONE, 2025)
Reducing the number of immunosuppressive cells in blood is a potential strategy for activating anti-tumor immunity, which provides a promising approach to cancer treatment. In this study, we developed an adsorbent designed to selectively target and adsorb lymphocytes expressing latency-associated peptide (LAP), which is abundantly expressed on the surface of CD4 + regulatory T cells (Tregs) and CD14 + monocytes. We investigated whether diethylenetriamine-conjugated polysulfone adsorbent-based direct hemoperfusion (DHP) enhances anti-tumor immunity in a rat cancer model with KDH-V liver cells. Our findings revealed that DHP significantly reduced LAP + Tregs in both peripheral blood and tumor tissues in treated mice. Consequently, cytotoxic T-lymphocytes increased in tumor-bearing rats. The anti-tumor effect was negated by the addition of cells detached from the absorbent, indicating that these cells play a crucial role in inhibiting the observed therapeutic effect. The results suggest that depleting LAP + immunosuppressive cells in blood can enhance anti-tumor immunity and improve survival of patients.